Tinjauan Filsafat Hukum Islam terhadap Sanksi Pidana Delik Kondermoord Pasal 342 KUHP - Latifah, Nani (Al-Jinayah : Jurnal Hukum Pidana Islam, 2018)
The article discusses a review of Islamic legal philosophy towards offense sanctions in the form of the Article 342 of the Criminal Code ". Kindermoord criminal sanctions Article 342 of the Criminal Code, namely murder carried out by a mother intentionally planning her intentions for a child / baby who will or not be born soon because of fear of being found out by another person, imprisoned for a maximum of nine years. In Islamic law the criminal sanctions of deliberate murder are qisas. However, in the offense of the victims' kind is the biological child of the offender, the sanctions imposed depend on the fulfillment of the conditions. In Islamic criminal law, qi??? punishment can be erased if the one who kills the victim's parents. If the basic sentence cannot be dropped, then instead it includes the ta'zir sentence whose form of punishment is fully handed over to Ulul ul Amri or the ruler with a record in the interest of the community. In the philosophy of Islamic law, the sanctions for the kindermoord offense include jar?mah ta'zir. Where the sentence is relevant to the legal objectives, namely the attainment of the benefit of the people, as a punishment that can give a deterrent effect to the perpetrators, so as to bring goodness to the community as a whole and preventive functioning of the possibility of repetition of the same type of crime, and repressively educating the perpetrators the good and realize the mistake. So that a judge in taking policy in punishment is adjusted to the benefit of the people based on the value of justice